Crossflow Ultrafiltration for Removing Direct-15 Dye from Wastewater of Textile Industry - A.L. Ahmad; S.W. Puasa; S. Abiding (Universitas Gadjah Mada, 2006)
Ultrafiltration membrane was used to treat the effluent from textile industries. Crossflow ultrafiltration using GN polymeric membrane was used to remove the dye from textile effluent. A synthetic textile effluent of Direct-15 dye was used. The study focused through the effect of feed concentration, transmembrane pressure and solution’s pH on the permeate flux and percentage of dye removal were investigated. Dye concentration had significant effects on flux values. Under the fixed pressures and pH, the flux decreased while the dye rejection increased with increasing feed concentration. Transmembrane pressure also had significant effect on flux values. Under the fixed feed concentration and pH, the flux increased while dye rejection decreased with increasing pressure. Experiment data showed that the highest flux was observed at pH 4 (acidic condition) while the highest dye removal observed at pH 7. Data collection could be used to improve the effectiveness of dye removal from textile industry wastewater using membrane technology.